PREVENTION OF STUNTING IN RURAL FAMILIES: LITERATUR REVIEW - Sulton Wariin; Tantut Susanto; Iis Rahmawati (UPT Penerbitan Universitas Jember, 2023)
Background: The high prevalence of stunting is still a health problem that is often discussed by people in developing countries. Factors related to stunting have been sought using a variety of methods. This study aims to identify the dominant factors that families can do related to stunting prevention in children. Methods: This research used relevant databases including PubMed, ScienceDirect, SAGE journals, and Google Scholar. Result: 15 articles were entered. Factors affecting stunting in families in rural areas are explained in the categories of maternal education, nutritional intake patterns, family size, and absence of latrines and safe water. Conclusions: The findings of this study show that several factors that influence the incidence of stunting or several studies that show a significant relationship between variables can be applied and adjusted at the family level in preventing stunting where the family is the smallest social environment that takes care of children 24 hours. Further studies are needed to identify more specific family functions in preventing Keywords: Family, Stunting Prevention Factors